Upaya meningkatkan Prestasi Belajar Matematika menggunakan Model Pembelajaran Think-Pair-Share Pokok Bahasan Kubus dan Balok pada Peserta Didik Kelas VIII SMP “Nurul Haq” Yapis Wamena - Sutarman Borean; Merlindaros S. Mangguali; Amos Rombe; Christine M. Rumpaisum; Citra R. Napitupulu (INTELEKTIUM, 2024)
This study aims to improve the learning achievement of students of class VIII B SMP "Nurul Haq" Yapis Wamena in studying mathematics subjects on the subject of volume of cubes and beams. The formulation of the problem in this study is whether the cooperative learning model type think-pair-share can improve the achievement of students. The type and technique of data analysis in this research is descriptive qualitative and quantitative combined data analysis. Data collection was done through tests, observation, and documentation. Based on the results of the study, it was concluded that efforts to improve students' learning achievement using the think-pair-share cooperative learning model were considered successful in accordance with the research indicators where 80% of students had reached the KKM standard. Even though there are still some students with increased learning achievement not in accordance with expectations, in this study the benchmark is the increase in the average score of students from cycle I to cycle II so that it can be concluded that the use of cooperative learning model type think-pair-share succeeded in improving the learning achievement of students of class VIII B SMP "Nurul Haq" Yapis Wamena.